1969
DOI: 10.1136/gut.10.9.730
|View full text |Cite
|
Sign up to set email alerts
|

Action of gastrin on the lower oesophageal sphincter in man

Abstract: suMMARY Both hog gastrin and synthetic gastrin stimulate the cardiac sphincter to increase tone and augment the resistance to reflux. Endogenous gastrin has a similar effect, and gastrin also stimulates the secretion of acid which has also been found to increase the resistance of the sphincter, but the effect of gastrin appears to be independent of the secretory stimulus.Now that the role of gastrin in the control of gastric acid secretion has become clearer, attention has turned to the subsidiary action of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
1
1

Year Published

1971
1971
1978
1978

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(41 citation statements)
references
References 15 publications
0
39
1
1
Order By: Relevance
“…The lower esophageal sphincter contracts in response to gastrin (12)(13)(14) whereas both the ileocecal (15) and choledochal sphincters (16) (25) and suggested that contaminants present in the GIH Research Unit preparation of cholecystokinin were not solely responsible for the observed response (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower esophageal sphincter contracts in response to gastrin (12)(13)(14) whereas both the ileocecal (15) and choledochal sphincters (16) (25) and suggested that contaminants present in the GIH Research Unit preparation of cholecystokinin were not solely responsible for the observed response (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…The most likely mechanism by which the pylorus serves this protective function would be the release of the duodenal hormones, secretin and cholecystokinin, in response to acidification. This would be analogous to the role of gastrin in maintaining lower esophageal sphincter competence (12)(13)(14). However, other hormonal or neural pathways can not be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that the gastrointestinal hormone, gastrin, has a physiological role in the control of sphincter strength (5,6). Since a well-known relationship exists between gastrin and secretin in the hormonal control of gastric acid secretion (7)(8)(9)(10)(11)(12) and gastric motor function (13)(14), it seemed possible that these hormones also interact to regulate lower esophageal sphincter competence.…”
Section: Introductionmentioning
confidence: 99%
“…The role of gastrin in the physiologic regulation of lower esophageal sphincter pressure (LESP)' is controversial (1)(2)(3)(4)(5)(6)(7)(8). Some observers have proposed that circulating gastrin (3,4) is the major determinant of LESP.…”
Section: Introductionmentioning
confidence: 99%